Numerical Study of The Power Plant Surface Condenser to Prevent High Pressure in Critical Areas - Eky Novianarenti; Ary Bachtiar Khrisna Putra; Setyo Nugroho; Arrad Ghani Safitra; Rini Indarti; Priyambodo Nur Ardi Nugroho; Mohammad Basuki Rahmat (Mechanical Engineering Department - Institut Teknologi Adhi Tama Surabaya, 2021)
A numerical study to reduce the condenser pressure in critical areas of a power plant surface condenser has been carried out. Numerically, effects are considered through a three-dimensional simulation approach. Modifying by adding a guide plate with a three variation of angle, (?) 15?, 30?, 45? in the surface condenser area to reduce the dynamic forces and pressure due to the collision of fluid flow in the critical pipeline without reducing the purpose of the design of shell and tube heat exchanger results in transferring heat. The drag force caused by the interaction of the shear layer with the surface of the body is very undesirable, so that the control of the flow fields is needed, one of which is by optimal angle guide plate of the pipe arrangement in the critical area. This study aims to determine the optimal plate angle to overcome high pressure in the critical area. This research was numerically conducted using 3D CFD ANSYS 14.5 software with a turbulence model using a standard k-? using a pressure-based solution solver. The initial stage takes geometric data on the surface condenser in the design specification as the basis for making the domain and data from before as boundary conditions in the simulation research process. The result is that with the addition of guide plates, the average drag coefficient (Cd) is reduced compared to the average Cd in the baseline conditions and angle variation (?) 15?, 30?, 45? is 0.537; 0.644; 0.446; 0.464. Taking into this aspect, the most optimal plate angle is 30?. The simulation results show that changing the angle of the plate can reduce the Nusselt value than the baseline conditions.